Athletes at late stage rehabilitation have persisting deficits in plantar- and dorsiflexion, and inversion (but not eversion) after ankle sprain. (July 2019) - Abassi, Mohsen; Bleakley, Chris; Whiteley, Rod
Abstract: Objectives: Document reliability and normative data for a novel device measuring weight-bearing ankle range of motion after ankle injury. Design: Cross-sectional Cohort, two occasions one day apart. Setting: Sports medicine hospital. Participants: 87 ankle-injured male athletes at a late stage of their rehabilitation and 25 uninjured subjects. The injured athletes had met all criteria to return to functional, on-field rehabilitation. Main outcome measures: Reliability (Intra-Class correlation Coefficient (ICC), and Minimum Detectable Change as a percent of the grand mean), weight-bearing range of motion (degrees) of dorsiflexion, plantarflexion, inversion, and eversion. Results: Good (dorsiflexion = 0.82[0.76–0.87] and inversion = 0.81[0.75–0.86]) and excellent (plantarflexion = 0.93[0.90–0.95]) reliability was documented, however reliability for the eversion measure showed only fair reliability (0.61[0.49–0.70]). Reduced range of motion in the injured leg was seen in all 4 directions, however with different magnitudes: Large differences were plantarflexion (−8.5°, ES = 0.80), medium for dorsiflexion (−5.2°, 0.57), small for inversion (−4.8°, 0.36), and trivial for eversion (−1.7°, 0.15). Conclusion: The device demonstrated clinically useful reliability for measuring these ranges of motion in a functional, weight-bearing position. PF ROM showed the greatest reduction in range in these athletes at a late stage of their rehabilitation. Highlights: The device measures weight-bearing ankle ROM with excellent reliability for DF, PF and inversion, & good reliability for eversion. Normative data are provided for a relatively large cohort of male athletes's ankle range of motion for these 4 movements. Despite meeting functional sports-specific goals, weight-bearing PF ROM remains diminished in comparison to the healthy leg.